The situation of the Hungarian apricot farming and its developmental tendencies - Pleszkó, Réka (Acta Agraria Debreceniensis, 2014)
The EC has declared „gönci magyar kajszi” as a product of specific origin with geographicald enomination. The „pálinka”isregistered Hungarian productin the EU. The micro-region of apricot production, named Gönc, has the privilege to utilize the great potential for rural development by its apricot production. To determine the development potential connected to apricot, needs through investigations on apricot production.This paper investigate apricot production at global, European and national levels. At national level each key aspects of apricot production have been analized. The final conclusions referring to Gönc micro-regionare: Northern Hungary region has got the biggest apricot area(within that Gönc has got outstanding role). The share of apricot cultivars of gönci origin ”has got overwhelming role in the Hungarian Cultivar assortment, the living tradition of production in this micro-region makes it possible, that gönci apricot will contribute to the overall socio-economic development in the region to a remarkable extend.